Evaluation of p-nitrophenyl substituted semicarbazones for anticonvulsant properties - Pandeya S.N.; Ponnilavarasan I.; Pandey A.; Lakhan R.; Stables J.P. (My University, 2025)
A series of p-nitrophenyl substituted semicarbazones has been synthesised and their anticonvulsant activity was screened against MES, scPTZ and scSTY. 4(4'-Nitrophenyl)-o-nitrobenzaldehyde semicarbazone has been found to be the most active in all these tests. The studies revealed that a primary amino function is not essential for anticonvulsant activity in the semicarbazone series of compounds. Presumably these compounds could further act on glycine receptors.